ANALISA PERBEDAAN KINERJA KEUANGAN PROFITABILITY RATIO PERUSAHAAN PARTISIPAN INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) 2009-2011 - Innesa Agustina (Business Accounting Review, 2014)
In this era, there is a change in business environment in which people want companies not only to pay attention about the profit but also to be responsible to the social and environmental aspects. Sustainability is a balance between people-planet-profit. Sustainability report is becomimg a trend for the company. For the purpose to assist, to develop,to measure, and to report the Sustainability report of each company, then the NCSR is formed. One of the activities held is the Indonesia Sustainability Reporting Award (ISRA).This study aimed to know whether there were differences in the financial performance measured using profit margin, ROA, and ROE of the company which participated in ISRA 2009-2011. The sample was 30 companies and were divided into categories of participating , sector , and labor. The result showed that there was differences in terms of the ROA in sector category. In participate and labor categories, there were no differences with profit margin, ROA, and ROE. In sector category, profit margin and ROE show there were no difference.